2011
DOI: 10.1017/s0144686x10001273
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' concerns about cognitive health: commonalities and differences among six United States ethnic groups

Abstract: We studied concerns about cognitive health among ethnically diverse groups of older adults. The study was grounded in theories of health behaviour and the representation of health and illness. We conducted 42 focus groups (N=396, ages 50+) in four languages, with African Americans, American Indians, Chinese Americans, Latinos, Whites other than Latinos (hereafter, Whites) and Vietnamese Americans, in nine United States locations. Participants discussed concerns about keeping their memory or ability to think as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…Our caregivers explained their reluctance mainly because of their sense of family responsibility. While it was not openly discussed among our participants, it has been suggested that reluctance of using nursing care among Asian Americans could be due in part to the concern for being seen by the community as abandoning their responsibility, an act that brings shame to family (Laditka et al, 2011;Liu et al, 2008). As sense of shame is known to influence help-seeking of Asian Americans, health care professionals need to be cognizant of this cultural belief in working with Korean American families.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our caregivers explained their reluctance mainly because of their sense of family responsibility. While it was not openly discussed among our participants, it has been suggested that reluctance of using nursing care among Asian Americans could be due in part to the concern for being seen by the community as abandoning their responsibility, an act that brings shame to family (Laditka et al, 2011;Liu et al, 2008). As sense of shame is known to influence help-seeking of Asian Americans, health care professionals need to be cognizant of this cultural belief in working with Korean American families.…”
Section: Discussionmentioning
confidence: 97%
“…There is also an indication of denial and fear to face the disease that may lead to reluctance among some Korean Americans to seek formal assessment and diagnosis. Dementia is indeed, and understandably, one of the most feared diseases across other racial/ethnic groups (Laditka et al, 2011). It is essential that educational dementia intervention for Korean Americans addresses correct disease information as well as the importance and urgency of receiving timely clinical assessment and appropriate treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of social network will affect the quantity and quality of social network, and in turn, influence cognitive function. Meanwhile, traditional Chinese culture may impact the cognitive function of older adults by way of attaching strong stigma to dementia [48,49]. From the perspective of the transtheoretical model of behavior change [50], the negative perception of cognitive impairment may prevent Chinese older adults from engaging in seeking behaviors for cognitive impairment in early stage.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the globally increasing proportion of older adults, the question of how to offset and even reverse structural and functional decline is steadily gaining in importance. Understandably, retaining cognitive health into older adulthood is of great concern to most older adults [1]. Both scholarly and commercial interest has been vested in identifying ways in which cognition can be stimulated in a way that can promise transfer to real-world tasks and activities.…”
Section: Introductionmentioning
confidence: 99%